Biodegradation of Polyester Polyurethane by Embarria clematidis - Khruengsai, Sarunpron; Sripahco, Teerapong; Pripdeevech, Patcharee (Frontiers in Microbiology, 2022)
This work investigates the biodegradation efficiency of 34 fungal species to degrade polyester polyurethane (PUR) as compared to Asgergillus niger, which served as the positive control. Eleven fungi are shown to degrade PUR in both solid- and liquid-medium assays. The highest degradation was attributed to Embarria clematidis cultured with PUR as a carbon source. The degradation was analyzed by sturm test, FTIR spectroscopy, and GC-MS. The amount of CO2 in E. clematidis with PUR after a 2-week incubation period (0.85 g/L) was much higher compared to the amount obtained from A. niger in the same conditions (0.53 g/L). Moreover, the degradation of soft segment and breakdown of urethane linkages were observed, as evidenced by the decrease of the carbonyl (1715 cm-1) and N-H stretching (1340 cm-1 and 1020 cm-1) FTIR spectral peaks, respectively. GC-MS detected 5Z-octenol, 2E,4E-hexadienol acetate, 3Z-hexenyl isobutanoate, phenyl-tert-butanol, and 3E,6Z-nonadienol as degradation products from the E. clematidis culture in PUR with higher intensity than those observed in PUR liquid medium without the fungi culture. The fungus was screened for their ability to produce extracellular esterase, protease, and urease enzymes. Extracellular esterase, very low urease, and no protease activities were detected in the culture supernatant of E. clematidis in the presence of PUR. The fungus E. clematidis is a promising source for PUR degradation, exhibiting significantly high levels of biodegradation.